(untitled) (Al-Mashadir: Journal of Quranic Sciences and Tafsir, 2025)
This research explores the urgency of developing contemporary religious expression through the cultivation of inclusivism values and attitudes as a foundation for fostering openness and mutual understanding within the context of human brotherhood. This study reveals that inclusivistic attitudes generate three fundamental values: personal values, social values, and religious values characterized by high tolerance. This research demonstrates that implementing inclusivistic attitudes is a crucial element requiring collective understanding across religious and social groups. Analysis of the Qur’an reveals various references emphasizing the importance of strengthening brotherhood bonds, both in the context of faith and universal humanity. According to Sheikh ’Ali Jum’ah’s concept of "ra>bithatun musytarikah" (shared bonds), this research finds that human brotherhood transcends the barriers of gender, ethnicity, race, and religion. Furthermore, this study discovers that integrating the Qur’an’s textual perspective with contemporary thoughts on religious inclusivism produces a new framework for understanding the urgency of inclusive values and attitudes in the modern era. This study contributes to the development of more open and humanistic religious discourse while offering a theoretical foundation for building social harmony in plural societies. (justify).